2007
DOI: 10.2337/db06-1682
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor 7-Like 2 (TCF7L2) Is Associated With Gestational Diabetes Mellitus and Interacts With Adiposity to Alter Insulin Secretion in Mexican Americans

Abstract: OBJECTIVE-Variation in transcription factor 7-like 2 (TCF7L2) gene has been shown to be associated with type 2 diabetes and diabetes-related quantitative traits. We examined variation in a 0.1-Mb region surrounding marker DG10S478 for association with diabetes-related quantitative traits in 132 Mexican-American families of a proband with previous gestational diabetes mellitus (GDM). RESEARCH DESIGN AND METHODS-Study participantswere phenotyped by an oral glucose tolerance test (OGTT) and an intravenous glucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
93
0
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(101 citation statements)
references
References 22 publications
4
93
0
4
Order By: Relevance
“…The effect size for GDM reported by this group was similar to that reported in patients with T2D. 33 Watanabe et al 38 observed that the T allele of the rs12255372 variant was more frequent among 94 Mexican-American women with previous GDM compared with 58 control subjects. These results suggest that TCF7L2 may be involved in GDM.…”
Section: Transcription Factor 7-like 2 (Tcf7l2)supporting
confidence: 64%
“…The effect size for GDM reported by this group was similar to that reported in patients with T2D. 33 Watanabe et al 38 observed that the T allele of the rs12255372 variant was more frequent among 94 Mexican-American women with previous GDM compared with 58 control subjects. These results suggest that TCF7L2 may be involved in GDM.…”
Section: Transcription Factor 7-like 2 (Tcf7l2)supporting
confidence: 64%
“…In addition, a similar association was found in a meta-analysis of four studies (Watanabe et al, 2007;Cho et al, 2009;Papadopoulou et al, 2011;Vcelak et al, 2012) regarding the T allele of rs12255372 and GDM risk; the pooled OR was 1.46 (95% CI 1.15 -1.84, P ¼ 0.002), without significant heterogeneity across studies (I 2 ¼ 48.3%; P for the Q statistic ¼ 0.122; Table IV, Fig. 2B).…”
Section: Genes and Genetic Variants Related To Insulin Secretionmentioning
confidence: 54%
“…Several previous reviews have mainly focused on the evidence regarding T2DM-associated common variants and GDM susceptibility (Watanabe et al, 2007;Robitaille and Grant, 2008;Konig and Shuldiner, 2012;Mao et al, 2012). Our systematic review provided a more comprehensive summary of the currently available evidence regarding GDM genetic variants.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have examined candidate genes in women with and without GDM. Positive associations were shown for genes encoding glucokinase [11], calpain-10 [12], sulfonylurea receptor 1 [13], potassium inwardly rectifying channel, subfamily J, member 11 (KCNJ11) [14], β 3 adrenergic receptor [15], plasminogen activator inhibitor 1 [16] and transcription factor 7-like 2 (TCF7L2) [17,18]. Except for the effects of TCF7L2 in Scandinavian women [17], no robust associations of genetic variants with GDM have been demonstrated.…”
Section: Introductionmentioning
confidence: 99%